3β-Acetyloxy-oleanolic Acid Attenuates Pristane-Induced Lupus Nephritis by Regulating Th17 Differentiation. (22nd May 2019) - Zhou, Xiaoqing; Chen, Huanpeng; Wei, Fengjiao; Zhao, Qingyu; Su, Qiao; Liang, Jinhao; Yin, Meng; Tian, Xuyan; Liu, Zhonghua; Yu, Bolan; Bai, Chuan; He, Xixin; et al.
Abstract : Th17 activity has been implicated in systemic lupus erythematosus (SLE), which is a systemic autoimmune disease with a typical clinical manifestation of lupus nephritis (LN). Retinoic acid receptor-related orphan receptor gamma t (ROR γ t) has been shown to be important for Th17 differentiation. In this study, we evaluated the inhibition of ROR γ t activity by 3 β -acetyloxy-oleanolic acid (AOA), a small molecule isolated from the root of Symplocos laurina, a traditional herb belonging to South China. We demonstrated that AOA can inhibit ROR γ t activity and prevent SLE pathogenesis in a pristane-induced LN model. The results showed that AOA decreased ROR γ t transcription activity in a reporter assay and prevented Th17 differentiation in vitro . In vivo studies showed that AOA treatment decreased serum anti-dsDNA antibody and alleviated renal pathologic damage as well as antibody complex accumulation in the pristane-induced LN model. These results demonstrated that AOA can improve the clinical manifestation of LN, indicating potential application in SLE therapy.